PENGARUH EFISIENSI PEMBERIAN AIR DAN PENAMBAHAN BAHAN ORGANIK TERHADAP PERTUMBUHAN DAN HASIL KACANG TANAH (Arachis hypogaea L) - Nur Aisah Cindy Lestari; Wahida Wahida (Musamus AE Featuring Journal, 2020)
ABSTRACT This study aimed to determine the land suitability class for soybean, corn and peanut plants in Kamno Sari Village, Jagebob District, Merauke Regency. Data analysis was carried out by matching or compare the land requirement for plant and the properties of the land in the study area. The results of this comparison shows the land suitability level for corn, soybeans and peanuts which includes S1 (very suitable), S2 (appropriate), S3 (marginally appropriate), N1 (not suitable at this time) and N2 (not suitable permanently). The results showed that the land suitability class for soybean plants on dry land, paddy fields and land that is planned to be cleared for planting, were classified as marginal suitability class (S3) with limiting factors for root media (r), nutrient retention (f) and available nutrients (n). On the land that is planned to be cleared for planting, the limiting factor is only available nutrients (n). While forest land and open land are included in the currently unsuitable class (N1) with a limiting factor of nutrient retention (f). Land suitability class for maize on dry land, paddy fields and planned land are classified as marginal suitability class (S3) with limiting factors for nutrient retention (f) and available nutrients (n), on planned land the limiting factor is only available nutrients (n), whereas forest and open land are included in the currently unsuitable class (N1) with a limiting factor of nutrient retention (f). Land suitability class for peanut plants on dry land, paddy fields and land plans are classified as marginal suitability class (S3) with limiting factors for root media (r), nutrient retention (f) and available nutrients (n). On the land plan the limiting factor only available nutrients (n), while forest land and open land are included in currently unsuitable class (N1) with a limiting factor is nutrient retention (f).